2004
DOI: 10.1063/1.1811379
|View full text |Cite
|
Sign up to set email alerts
|

Observation of fast spontaneous emission decay in GaInAsP photonic crystal point defect nanocavity at room temperature

Abstract: The spontaneous emission decay in a photonic crystal slab nanocavity with a GaInAsP quantum well active region was measured at room temperature. Even far below lasing threshold, the decay was much faster than that for the as-grown wafer. A consideration including the enhanced spontaneous emission rate by the Purcell effect, intraband relaxation of carriers, nonradiative surface recombination, spatial hole burning, and carrier diffusion enabled us to explain different decay lifetime between on-and off-resonant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…However, we have found that spatial effects such as carrier transport from the pump spot to the gain region, or spatial hole burning effects [25], are important in understanding lasing efficiency and time response. For that reason, we have developed a finite-difference time domain model that includes carrier dynamics.…”
Section: Rate Equations Model In Fdtdmentioning
confidence: 99%
“…However, we have found that spatial effects such as carrier transport from the pump spot to the gain region, or spatial hole burning effects [25], are important in understanding lasing efficiency and time response. For that reason, we have developed a finite-difference time domain model that includes carrier dynamics.…”
Section: Rate Equations Model In Fdtdmentioning
confidence: 99%
“…Besides the dramatically enhanced small-and large-signal modulation speeds, the QED-enhanced lasers can also significantly improve power consumption [13][14][15][16][17]23 and associated thermal problems. The large β reduces the threshold power of the laser 23 .…”
mentioning
confidence: 99%
“…Cavities introduced into the photonic crystal can have extremely high Q/V mode ratios, and therefore can enable large Purcell factors. So far, such nanocavities have been used for cavity quantum electrodynamic (QED) experiments 4-12 such as SE rate enhancement 4,5,9-11 and suppression 4 , and also for single-photon sources 4,12 and lower-threshold lasers [13][14][15][16][17] . Here, we demonstrate extremely fast photonic crystal nanocavity lasers with response times below the 2 ps detection limit of our measurement apparatus.…”
mentioning
confidence: 99%
“…Many studies were published in the last decade on the opti− mization of PhC nanocavities [42,43], on the possibility of measuring the Purcell effect by a PhC based nanocavity [44][45][46][47] and quite recently on their capability to act as effi− cient single photon sources [48]. An L3 defect cavity is formed by keeping three holes un−etched along the GK direction of a triangular PhC and parallel to a cleaved edge of the GaAs sample.…”
Section: Optical Excitationmentioning
confidence: 99%